Temuan Chromoendoscoy pada Espfagoskopi Diagnostik: Sebuah Serial Kasus - Puspa Zuleika; Adelien Adelien; Eriza Eriza; Daniel Bramantyo (Oto Rhino Laryngologica Indonesiana, 2026)
Background: Patients with head and neck squamous cell carcinoma (HNSCC) carry a significant risk for potential spread of malignancy to the aerodigestive tract. Lugol chromoendoscopy is a well-established image-enhanced technique that increases the sensitivity for detecting early synchronous esophageal squamous cell neoplasms (ESCNs) by selectively staining normal glycogen-rich epithelium brown, leaving dysplastic or malignant areas unstained. Purpose: To describe the findings of chromoendoscopy during diagnostic esophagoscopy in three patients diagnosed with laryngeal carcinoma, who were scheduled for total laryngectomy as a follow-up treatment. Case reports: We presented three cases of male patients diagnosed with Stage III laryngeal carcinoma. Case 1 and case 2 were scheduled for primary total laryngectomy. Case 3 was scheduled for total laryngectomy following post-chemoradiotherapy recurrence. All patients underwent diagnostic esophagoscopy to evaluate potential esophageal extension. Clinical question: “Is chromoendoscopy highly sensitive in detecting malignant spread in patients with head and neck squamous cell carcinoma in the esophageal area?” Method: Literature search was conducted using key word “ chromoendoscopy” AND ”esophagoscopy” AND ”esophagus” AND ”therapy” in PubMed and Google Scholars. Exclusion criteria included articles published before the year 2000. Result: A total 30 articles relevant to this topic, and nine could be used as refferences. Conclusion: Chromoendoscopy is a highly effective diagnostic tool in the preoperative workup of laryngeal carcinoma patients. It significantly enhances the detection of both synchronous esophageal lesions and malignant extensions, enabling more precise surgical planning and comprehensive management, before major interventions such as total laryngectomy.